2016
DOI: 10.1080/15287394.2016.1193113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone on synaptic plasticity mediated by androgen receptors in male SAMP8 mice

Abstract: Synaptic changes are closely associated with cognitive deficits. In addition, testosterone (T) is known to exert regulative effects on synaptic plasticity. T may improve cognitive deficits in Alzheimer's disease (AD) patients, but the underlying mechanisms of androgenic action on cognitive performance remain unclear. The aim of this study was thus to examine the protective mechanism attributed to T on cognitive performance in an AD senescence, accelerated mouse prone 8 (SAMP8) animal model. Using Golgi stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 27 publications
1
27
0
2
Order By: Relevance
“…While the AR is abundantly expressed in both sexes, in AD expression of the AR has been found to be generally down-regulated, especially in aging males (Butchart et al, 2013; Dart et al, 2013; Fedotova et al, 2016; Jia et al, 2016). Interestingly the steroid-hormone testosterone-activated transcription factor-signaling AR (ANDR) is known to exert regulatory effects on synaptic plasticity and improve cognitive deficits in AD patients and transgenic rodent models for AD (TgAD) but the underlying mechanisms of androgenic action on cognitive performance remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the AR is abundantly expressed in both sexes, in AD expression of the AR has been found to be generally down-regulated, especially in aging males (Butchart et al, 2013; Dart et al, 2013; Fedotova et al, 2016; Jia et al, 2016). Interestingly the steroid-hormone testosterone-activated transcription factor-signaling AR (ANDR) is known to exert regulatory effects on synaptic plasticity and improve cognitive deficits in AD patients and transgenic rodent models for AD (TgAD) but the underlying mechanisms of androgenic action on cognitive performance remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly the steroid-hormone testosterone-activated transcription factor-signaling AR (ANDR) is known to exert regulatory effects on synaptic plasticity and improve cognitive deficits in AD patients and transgenic rodent models for AD (TgAD) but the underlying mechanisms of androgenic action on cognitive performance remain unclear. Testosterone, via the AR, increases synaptophysin expression and improves synaptic plasticity and cognitive metrics in both Aβ42 peptide-hippocampal injected male rats and in the senescence-accelerated mouse prone 8 (SAMP8) TgAD murine model (Huo et al, 2016; Jia et al, 2016). In a recent double-blind, placebo-controlled, between-subject designed study, exogenous administration of testosterone to healthy adult men potentiated the AR-enriched hippocampus, amygdala and hypothalamus—anatomical regions known to be involved in the stimulation of aggressive behavior (Carré et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…84 It has been reported that androgen receptors are involved in memory and learning by involving synapse function. 85,86 DHT could reduce the binding of N-methyl-D-aspartate (NMDA) receptor antagonist in hippocampus CA1 region, 87 and control NMDA mediated depolarization in pyramidal neurons. 88 Recent study reported that androgen inhibits reduction of hippocampal dendritic spine density in rats.…”
Section: Androgen Receptor Could Control Insulin Resistance and Synapmentioning
confidence: 99%
“…90 Also, testosterone could enhance the expression of brain derived neurotrophic factor, leading to improvement in hippocampal dendritic spine density, and the phosphorylation of CREB to enhance synaptic plasticity. 86 Androgens improve spine-synapse density in the CA1 of rodents. 91 Taken together, androgen could improve insulin resistance by binding androgen receptor in brain, enhance synaptic failure, and promote synaptogenesis in the AD brain.…”
Section: Androgen Receptor Could Control Insulin Resistance and Synapmentioning
confidence: 99%